2013
DOI: 10.1371/journal.pone.0069457
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nuclear Morphometric Signature for Prostate Cancer Risk in Negative Biopsies

Abstract: BackgroundOur objective was to develop and validate a multi-feature nuclear score based on image analysis of direct DNA staining, and to test its association with field effects and subsequent detection of prostate cancer (PCa) in benign biopsies.MethodsTissue sections from 39 prostatectomies were Feulgen-stained and digitally scanned (400×), providing maps of DNA content per pixel. PCa and benign epithelial nuclei were randomly selected for measurement of 52 basic morphometric features. Logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…A current difficulty in the area of diagnostic pathology of prostate and breast biopsy specimens is the differential diagnosis of the very small volume of tumor samples. Recent studies with nuclear morphometry techniques successfully detect the cancer field effect in adjacent tissue in both prostate and breast cancers allowing for detection of cancer without direct observation of a lesion [35][36][37][38]. Applying these types of technical advancements to the prognostic space, future studies using nuclear morphometry to detect the degree of mesenchymal transformation or EMT fraction of CTCs within a prostate biopsy may have considerable value in predicting patient outcome and appropriate course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A current difficulty in the area of diagnostic pathology of prostate and breast biopsy specimens is the differential diagnosis of the very small volume of tumor samples. Recent studies with nuclear morphometry techniques successfully detect the cancer field effect in adjacent tissue in both prostate and breast cancers allowing for detection of cancer without direct observation of a lesion [35][36][37][38]. Applying these types of technical advancements to the prognostic space, future studies using nuclear morphometry to detect the degree of mesenchymal transformation or EMT fraction of CTCs within a prostate biopsy may have considerable value in predicting patient outcome and appropriate course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this subjectivity, recent advances in imaging combined with machine learning have provided new avenues [103,104]. These include parametric machine-learning techniques that use quantitative nuclear morphometric information, such as nuclear size, shape, nucleus:cytoplasm ratio, and chromatin texture, for classifying histopathology images [105,106]. More recently, various nonparametric methods, including deep learning, have been applied for diagnosing various cancers, including breast, skin, and thyroid cancer, with high accuracies [107,108].…”
Section: Digital Nuclear Mechanopathology For Cancer Diagnosismentioning
confidence: 99%
“…There has been evidence to suggest that the microenvironment surrounding the prostate tumor may play a role in cancer progression [5,6], a phenomena known as the field effect . Epigenetic changes within the benign regions surrounding the tumor have been shown to be capable of initiating PCa [5].…”
Section: Introductionmentioning
confidence: 99%
“…Veltri et al [7] and Gann et al [6] showed that there are quantifiable morphometric attributes within tumor-adjacent benign regions that can provide additional information related to disease outcome. These studies, however, have been limited to the correlation of outcome and nuclear shape parameters alone.…”
Section: Introductionmentioning
confidence: 99%